Imaging of antitubercular dimeric boronic acids at the mycobacterial cell surface by click-probe capture. Issue 67 (2nd August 2022) - Guy, Collette S.; Tomás, Ruben M. F.; Tang, Qiao; Gibson, Matthew I.; Fullam, Elizabeth
Abstract : Antitubercular 'clickable' diboronic acid agents are directly incorporated into the mycobacterial cell envelope through glycan-targeting. Abstract : Dimeric boronic acids kill Mycobacterium tuberculosis ( Mtb ) by targeting mycobacterial specific extracellular glycans, removing the requirement for a therapeutic agent to permeate the complex cell envelope. Here we report the successful development and use of new 'clickable' boronic acid probes as a powerful method to enable the direct detection and visualisation of this unique class of cell-surface targeting antitubercular agents.